2019
DOI: 10.1104/pp.18.01092
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma Histone Deacetylase HDA-2 Modulates Multiple Responses in Arabidopsis

Abstract: Trichoderma spp. are a rich source of secondary metabolites and volatile organic compounds (VOCs), which may induce plant defenses and modulate plant growth. In filamentous fungi, chromatin modifications regulate secondary metabolism. In this study we investigated how the absence of histone deacetylase HDA-2 in the Trichoderma atroviride strain Dhda-2 impacts its effect on a host, Arabidopsis (Arabidopsis thaliana). The production of VOCs and their impact on plant growth and development were assessed as well. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 79 publications
4
38
0
2
Order By: Relevance
“…oxysporum-T. atroviride co-cultivation further resulted in the production of 2-octanone, a volatile that was not emitted by any of the interaction partners upon axenic growth. Interestingly, a recent study revealed that deletion of the histone deacetylase-encoding gene hda-2 in T. atroviride IMI 206040 leads to the biosynthesis of 2-octanone as a new volatile in this strain [43]. This report together with our results points out that 2-octanone biosynthesis genes could be shut-down by a repressive chromatin structure and could be activated epigenetically as a consequence of environmental stimuli, in this case the interaction with F. oxysporum.…”
Section: Discussionsupporting
confidence: 76%
“…oxysporum-T. atroviride co-cultivation further resulted in the production of 2-octanone, a volatile that was not emitted by any of the interaction partners upon axenic growth. Interestingly, a recent study revealed that deletion of the histone deacetylase-encoding gene hda-2 in T. atroviride IMI 206040 leads to the biosynthesis of 2-octanone as a new volatile in this strain [43]. This report together with our results points out that 2-octanone biosynthesis genes could be shut-down by a repressive chromatin structure and could be activated epigenetically as a consequence of environmental stimuli, in this case the interaction with F. oxysporum.…”
Section: Discussionsupporting
confidence: 76%
“…Successful establishment of the Trichoderma –plant interaction during early stages of root colonization implies the activation of cell detoxification and protection mechanisms in the fungi (Ruocco et al, 2009; Estrada-Rivera et al, 2019). Therefore, these fungi possess effective systems that efficiently scavenge harmful compounds from the cell.…”
Section: Trichoderma’s Small Rnas As Putative Effectorsmentioning
confidence: 99%
“…The expression of these genes is transient and decreased to levels of the control plants. Trichoderma resembles mycorrhizal fungi in the establishment of symbiotic associations rather than fungal pathogens (Masunaka et al, 2011; Estrada-Rivera et al, 2019). Production of sRNAs by filamentous fungi, including Trichoderma species, has been documented.…”
Section: Trichoderma’s Small Rnas As Putative Effectorsmentioning
confidence: 99%
“…are able to establish in the rhizosphere of host plants, leading to beneficial effects (Guzmán‐Guzmán et al , 2018). The growth‐promoting effects are based on mobilization of nutrients (Harman, 2011), induction of plant systemic resistance (Shoresh et al , 2010; Estrada‐Rivera et al , 2019), and a mycotrophic lifestyle towards plant pathogens (Druzhinina et al , 2011; Kubicek et al , 2011). Recent studies show very species‐specific volatile profiles for Trichoderma (Siddiquee et al , 2012; Lee et al , 2016; Guo et al , 2019), whose patterns can drastically change in interaction with other organisms (Guo et al , 2019), suggesting important ecological functions for fVOCs of Trichoderma .…”
Section: Introductionmentioning
confidence: 99%